Arabic Language Implementation Viewed from A Social and Cultural Perspective at Maitreechit Withayattan School Bangkok - Rusli, Radif Khotamir; Fauziah, R Siti Pupu; Martin, Abraham Yazdi; Lathifah, Zahra Khusnul; Helmanto, Fachri; Mukminin, Amirul (Universitas Negeri Makassar, 2024)
This research explores the implementation of Arabic language learning at the Maitreechit Withayattan School in Bangkok, Thailand. With a population dominated by a Muslim minority, this research aims to understand the challenges and potential for developing Arabic language education in this context. The research background reflects Thailand's uniqueness as an ASEAN country with a Muslim minority that is recognized and regulated by national law. The focus of the research is on issues of student interest, teaching methods, hidden learning goals, and the role of teachers in the learning process. The research method uses modern ethnographic studies at Maitrechit Wittaayathan School Bangkok. Research findings show that students' low interest is influenced by less innovative teaching methods and a need for more variety in learning. Hidden learning goals, which include students' political aspirations to support the position of Muslims in government, become a complex dynamic in Arabic language learning. The importance of Arabic in the government context was a significant finding, with students being taught that Arabic language skills can provide a competitive advantage in careers in the government sector. Despite challenges regarding student interest, school administrators' high enthusiasm for Arabic creates the potential for solid collaboration between education and religious identity development. Implications for Arabic language education management include the need for more exciting learning strategies, teacher training, and collaboration with external parties to increase the relevance of learning to careers. This research provides in-depth insight into the complex dynamics of Arabic language education in Muslim minority school environments in Thailand. However, it should be acknowledged that the research findings are limited to one school in Bangkok, and generalization of the findings must be done cautiously.